2022
DOI: 10.1021/acs.analchem.2c01560
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Potential of Helmholtz and Planar NMR Microcoils for Analysis of Intact Biological Samples

Abstract: Nuclear magnetic resonance (NMR) spectroscopy has played an integral role in medical and environmental metabolic research. However, smaller biological entities, such as eggs and small tissue samples, are becoming increasingly important to better understand toxicity, biological growth/development, and diseases. Unfortunately, their small sizes make them difficult to study using conventional 5 mm NMR probes due to limited sensitivity. The use of microcoil NMR holds great potential for the analysis of such sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…However, if a planar coil is already oriented horizontally to create a field along X , Y , it must generate a field that runs across its surface rather than perpendicular to it. Practically, all NMR microcoils designed to date are aligned vertically and generate perpendicular B 1 fields. ,,, As such, before a horizontal DMF system can be considered, it must be determined whether a horizontal planar coil can be designed with acceptable lineshape, sensitivity, and penetration depth. Ultimately, the questions become “how compromised is the NMR performance of horizontal coils when compared to vertical orientations?” as well as “are these losses acceptable for in vivo DMF-research?”…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if a planar coil is already oriented horizontally to create a field along X , Y , it must generate a field that runs across its surface rather than perpendicular to it. Practically, all NMR microcoils designed to date are aligned vertically and generate perpendicular B 1 fields. ,,, As such, before a horizontal DMF system can be considered, it must be determined whether a horizontal planar coil can be designed with acceptable lineshape, sensitivity, and penetration depth. Ultimately, the questions become “how compromised is the NMR performance of horizontal coils when compared to vertical orientations?” as well as “are these losses acceptable for in vivo DMF-research?”…”
Section: Resultsmentioning
confidence: 99%
“…Microcoil NMR is one possible method to address these mass sensitivity issues. Surface microcoils are particularly interesting as the sample sits directly on top, increasing mass sensitivity due to the proximity to the coil surface, and they can be easily redesigned to match a wide range of specific sample sizes. , Previous research has shown that matching the size of the coil to the sample size can increase sensitivity by two to three magnitudes. In turn, the additional mass sensitivity should require fewer organisms. This is especially important as in vivo NMR monitoring requires 2D 1 H- 13 C experiments to provide the additional chemical shift dispersion and in turn allow a range of metabolites to be assigned and monitored .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape of the nutation curve provides valuable insight into both the intensity and, in some cases, the homogeneity of the magnetic field. For example, poor B 1 homogeneity is a common challenge with planar surface microcoils <1000 μm, where samples often experience inhomogeneous excitation leading to nutation curves with poor or no inversion. , This becomes problematic when analyzing biological samples where the complex metabolic profile and high water content often necessitate the use of more complex pulse sequences that require inversion and/or phase-cycled cancellation. , This makes it difficult to use 500 μm planar microcoils to study small biological samples. In contrast, the Lenz lens designed here for samples <500 μm produces a sinusoidal nutation curve with excellent inversion over the critical 0–360° window, consistent with a uniform and intense field across the entire sample.…”
Section: Resultsmentioning
confidence: 99%
“…32,39−42 This becomes problematic when analyzing biological samples where the complex metabolic profile and high water content often necessitate the use of more complex pulse sequences that require inversion and/or phase-cycled cancellation. 40,43 This makes it difficult to use 500 μm planar microcoils to study small biological samples. In contrast, the Lenz lens designed here for samples <500 μm produces a sinusoidal nutation curve with excellent inversion over the critical 0−360°window, consistent with a uniform and intense field across the entire sample.…”
Section: ■ Introductionmentioning
confidence: 99%